Integrated Application of Innovative Technologies for Oil Spill Remediation in Gran Tarajal Harbor: A Scientific Approach - Jesús Cisneros-Aguirre; María Afonso-Correa (Waste)
This study examines recovery efforts at Gran Tarajal Harbor following a significant oil spill, employing a combination of innovative technologies tailored to enhance oil spill remediation. Cleanup operations incorporated advanced absorbent sponges with high reusability, absorbent granulates for targeted hydrocarbon capture, bioremediation techniques using allochthonous microorganisms to accelerate natural degradation processes, and the integration of newly designed oil containment barriers coupled with sponges. These technologies were instrumental in effectively mitigating environmental damage, as evidenced by a reduction in hydrocarbon concentrations in sediments from nearly 60,000 mg/kg to under 1600 mg/kg within seven months. Notably, advanced absorbent sponges demonstrated superior capacity for repeated use, optimizing the cleanup process and contributing to the sustainability of the response efforts. The most important finding of this research is the demonstrated efficacy of integrated approach in not only reducing hydrocarbon contamination but also in promoting ecological recovery. Heavy metal analyses revealed that lead and copper concentrations were primarily associated with routine port activities, while mercury levels, attributed to the spill, decreased significantly over time. Tissue analysis of local organisms showed minimal contamination, and assessments of biological communities indicated signs of ecological recovery. This work highlights the necessity of introduce new disruptive technologies in contingency plans.